Assessing Protein Synthesis and Degradation Rates in Arabidopsis thaliana Using Amino Acid Analysis. Issue 5 (17th May 2021) - Ishihara, Hirofumi; Moraes, Thiago A.; Arrivault, Stéphanie; Stitt, Mark
Abstract: Plants continually synthesize and degrade proteins, for example, to adjust protein content during development or during adaptation to new environments. In order to estimate global protein synthesis and degradation rates in plants, we developed a relatively simple and inexpensive method using a combination of 13 CO2 labeling and mass spectrometry–based analyses. Arabidopsis thaliana plants are subjected to a 24‐hr 13 CO2 pulse followed by a 4‐day 12 CO2 chase. Soluble alanine and serine from total protein and glucose from cell wall material are analyzed by gas chromatography time‐of‐flight mass spectrometry (GC‐TOF‐MS) and their 13 C enrichment (%) is estimated. The rate of protein synthesis during the 13 CO2 pulse experiment is defined as the rate of incorporation of labeled amino acids into proteins normalized by a correction factor for incomplete enrichment in free amino acid pools. The rate of protein degradation is estimated as the difference between the rate of protein synthesis and the relative growth rate calculated using the 13 C enrichment of glucose from cell wall material. Degradation rates are also estimated from the 12 CO2 pulse experiment. The following method description includes setting up and performing labeling experiments, preparation and measurement of samples, and calculation steps. In addition, an R script is provided for the calculations. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Setting up the 13 CO2 labeling system and stable isotope labeling of Arabidopsis thaliana rosette leaves Basic Protocol 2 : Extraction of soluble amino acids for GC‐TOF‐MS analysis Basic Protocol 3 : Preparation of amino acids from total protein for GC‐TOF‐MS analysis Basic Protocol 4 : Preparation of sugars from cell wall material for GC‐TOF‐MS analysis Basis Protocol 5 : GC‐TOF‐MS analysis of 13 C‐labeled samples and estimation of 13 C enrichment (%) Basis Protocol 6 : Estimation of protein synthesis and degradation rates